Comparison of three-jet events in pp̄ collisions at √s = 1.8 TeV to predictions from a next-to-leading order QCD calculation - Acosta, D; Affolder, T; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Ashmanskas, W; Azfar, F; et al. (2005)
The properties of three-jet events with total transverse energy greater than 320 GeV and individual jet energy greater than 20 GeV have been analyzed and compared to absolute predictions from a next-to-leading order (NLO) perturbative QCD calculation. These data, of integrated luminosity 86 pb -1, were recorded by the CDF Experiment for pp collisions at √s = 1.8 TeV This study tests a model of higher order QCD processes that result in gluon emission and may give some indication of the magnitude of the contribution of processes higher than NLO. The total cross section is measured to be 466 ± 3(stat.)-70+207(syst.) pb. The differential cross section is furthermore measured for all kinematically accessible regions of the Dalitz plane, including those for which the theoretical prediction is unreliable. While the measured cross section is consistent with the theoretical prediction in magnitude, the two differ somewhat in shape in the Dalitz plane. © 2005 The American Physical Society.